Effects of different combinations of antibacterial compound supplements in calf pellets on growth performance, health, blood parameters, and rumen microbiome of dairy calves - Li, Shujie; Wang, Changjian; Zeng, Hanfang; Han, Zhaoyu (Frontiers in Veterinary Science, 2024)
This study investigated the effects of different combinations of antibacterial compounds (attapulgite, plant essential oils, and chitosan oligosaccharides) on growth performance, blood biochemical parameters, and rumen microbiome of calves. A total of 48 preweaning calves were randomly divided into four groups (n =12 per group), and fed the following full mixed-ration granule diets for the 67-d-feeding trial: (1) basal diet (control group); (2) basal diet + 1000 g/t attapulgite, plant essential oils, and chitosan oligosaccharide (AEOCO group); (3) basal diet + 1000 g/t attapulgite and chitosan oligosaccharide (ACO group); and (4) basal diet + 1000 g/t attapulgite and plant essential oil (AEO group). The results showed that the daily weight gain of the AEOCO and AEO groups significantly increased (P < 0.05), whereas the feed conversion ratio decreased compared with that of the control group. Among the three treatment groups, AEO group showed the most positive effect, with the diarrhea rate reduced by 68.2% compared with that of the control group. Total protein and globulin levels were lower in the AEO group than in the control group. Albumin levels were higher in the AEOCO and AEO groups than in the control group. Immunoglobulin A, immunoglobulin G, and immunoglobulin M concentrations were higher in the AEOCO group (P < 0.05) than in the control group. The interleukin-6 concentration was lower in the AEOCO and AEO groups than in the control group (P < 0.05). The Chao 1 richness and ACE indices were higher in the AEOCO group than in the control group (P < 0.05). The ACO group had a significantly lower (P < 0.05) relative abundance of Firmicutes than the control group. The relative abundance of Bacteroidetes was the lowest in the control group, whereas that of Spirochaetota and Fibrobacteriota was the highest (P < 0.05). The relative abundance of Succiniclasticum was higher in the ACO and AEO groups (P < 0.05). These findings indicate that the combination of attapulgite, plant essential oils, and chitosan oligosaccharides has ameliorative effects on the growth performance, blood parameters, and rumen microbiome of calves.